Pampango personal pronouns, a descriptive analysis - Tecson, Consuelo H. 1915- (s.n.], 1966)
A detailed description of Pampango personal pronouns is provided in this study. Pampango personal pronouns are nine in number, namely: aku, ikami, itamu, ika, ikayu, ikata, iya, ita, and ila. These pronouns are classified according to person, number, and ease.